Les facteurs cognitifs inhérents à l’expertise du traducteur - Salem Moughayar, Carine (Studia Romanica Posnaniensia, 2019)
This study investigates the differences between novice and expert translators. Six expert translators and six translation students were asked to translate a text into Arabic and explain their translation process. The results show a difference in the translation quality, expertise of translation and the way novices and experts think and solve the translation problems. Numerous factors such as memory, emotions, decision making, problem solving, etc. co-determine successful experts. A translator expert is not just someone who has translation skills, it’s also someone who understands how his knowledge is organized; he behaves automatically and fluidly without conscious control.